2012
DOI: 10.1016/j.jnoncrysol.2011.12.113
|View full text |Cite
|
Sign up to set email alerts
|

Low temperature plasma deposition of silicon thin films: From amorphous to crystalline

Abstract: We report on the epitaxial growth of crystalline silicon films on (100) oriented crystalline silicon substrates by standard plasma enhanced chemical vapor deposition at 175 °C. Such unexpected epitaxial growth is discussed in the context of deposition processes of silicon thin films, based on silicon radicals and nanocrystals. Our results are supported by previous studies on plasma synthesis of silicon nanocrystals and point toward silicon nanocrystals being the most plausible building blocks for such epitaxia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 25 publications
5
26
0
Order By: Relevance
“…We obtained the same results for silicon films, for which conditions known to lead to hydrogenated polymorphous silicon (pm-Si:H) on glass lead to epitaxial growth when applied to (100)-oriented Si substrates [17,18,21]. Other research groups also found that a rather broad range of experimental parameters would eventually lead to unwanted epitaxial films on (100) Si substrates [22,23].…”
Section: Resultssupporting
confidence: 66%
“…We obtained the same results for silicon films, for which conditions known to lead to hydrogenated polymorphous silicon (pm-Si:H) on glass lead to epitaxial growth when applied to (100)-oriented Si substrates [17,18,21]. Other research groups also found that a rather broad range of experimental parameters would eventually lead to unwanted epitaxial films on (100) Si substrates [22,23].…”
Section: Resultssupporting
confidence: 66%
“…This difference in growth mode between h100i and h111i surfaces is in line with earlier findings using PECVD. 37,38 The origin of this phenomenon has been elusive. Interestingly, this crystalline-orientation-dependent growth mode shows a striking resemblance with observations made for low-temperature epitaxial growth using MBE in ultrahigh vacuum conditions.…”
Section: A Determining Parameters For Epitaxial Growthmentioning
confidence: 99%
“…Note that the same process conditions on <100> c-Si substrates have been shown to lead to epitaxial growth48. The SE spectra were modeled using the Tauc-Lorentz dispersion model for amorphous materials4950, and the Bruggeman effective medium approximation (BEMA) was used to determine the composition of μc-Si:H films5152.…”
Section: Methodsmentioning
confidence: 99%